Nowe wyzwania dla ochrony praw człowieka - Czubik, Agnieszka; Dziwisz, Dominika; Szczepankiewicz-Rudzka, Ewa; Tarnawski, Marcin (2020)
The publication which we present to the reader was prepared by the employees of the Department of the Strategy of International Relations of the Jagiellonian University, lawyers and political scientists. It presents a multifaceted approach to new, frequently controversial and incompletely solved problems associated with the protection of human rights.